CAUSALITY OF CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE: A STUDY OF BSE LISTED COMPANIES - Om Prakash Agrawal, Prateek Kumar Bansal (International Journal of Modern Agriculture, 2020)
Present study tries to examine the relationship of corporate social responsibility and financial performance of the BSE Listed 30 companies of India. Usually companies in CSR integrate social and environmental concerns in their business activities and also addresses the expectations of shareholders. Financial performance can be measured by the ratios of different accounting components. Data of CSR expenditure from 2014-15 to 2017-18 of the 30 companies of BSE India have been collected through the website of Ministry of Corporate Affairs and measures of financial performance such as Net Sales, earning per share, Earning Yield, Net profit ratio, Current ratio and Return on capital employed has been taken to study the relationship. Statistical tools such as Correlation and regression has been used with the help of econometrics. Results shows the positive impact of financial performance on CSR because the expenditure on CSR usually dependent upon the financial performance.